Ser mãe é padecer no paraíso? O dispositivo da maternidade nas narrativas da depressão pós-parto - Cronemberger, Lorena Ferreira (2019)
Currently in Brazil, one in each four women is faced with the symptoms of postpartum depression. For Biomedicine and for Women's Mental Health Policies, the search for explanations and causalities are mainly from body and psychical order. But what about the women experiencing postpartum suffering? Hormones? Sadness? Disease? A male chauvinist society that overloads mothers? The present work is the result of a qualitative study on the meanings and experiences of postpartum depression by middle-aged women in the cities of Recife (State of Pernambuco) and João Pessoa (State of Paraiba). Through interviews that sought to penetrate the experience of pregnancy, childbirth and postpartum, we sought to analyze the significance of postpartum depression in order to perceive the intersection between health, gender and maternity, and what we will understand as being part of the maternity device, which is elaborated as an analytical tool that triggers instances of power and control over the body and maternal experience. For the presentation of the data, we divided the reports into two parts: the first introducing questions about pregnancy and childbirth, and the second on the postpartum and postpartum depression. The research suggests a plurality of meanings and emotions about motherhood, which can be captured from postpartum depression and include guilt, fatigue, fear, frustration, and ambivalent feelings.